1989
DOI: 10.1080/01688638908400882
|View full text |Cite
|
Sign up to set email alerts
|

Unawareness of deficits in neuropsychological syndromes

Abstract: Damage to different regions of the brain can cause a variety of neuropsychological deficits, including specific disturbances of language, memory, perception and motor function. A significant number of brain-damaged patients are unaware of their deficits, even when they are profound and have debilitating effects on patients' performance. This article reviews clinical observations and experimental investigations concerning unawareness of deficits, considers methodological issues, and critically evaluates differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
367
3
23

Year Published

1993
1993
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(406 citation statements)
references
References 136 publications
13
367
3
23
Order By: Relevance
“…These conjectured systems might either be integral with the functional domain for which awareness has been lost (i.e. modular Bisiach et al, 1990) or superordinate and centralised, able to influence awareness across a range of sensorimotor and cognitive functions (McGlynn & Schacter, 1989). In the latter case, even the invocation of partial disconnection cannot account for the clinical observation of patients with loss of awareness for some symptoms but not for others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These conjectured systems might either be integral with the functional domain for which awareness has been lost (i.e. modular Bisiach et al, 1990) or superordinate and centralised, able to influence awareness across a range of sensorimotor and cognitive functions (McGlynn & Schacter, 1989). In the latter case, even the invocation of partial disconnection cannot account for the clinical observation of patients with loss of awareness for some symptoms but not for others.…”
Section: Discussionmentioning
confidence: 99%
“…Several such theoretical accounts have been put forward. These can be fairly divided into psychodynamic or motivational theories (Weinstein & Kahn, 1955) and cognitive theories (Bisiach, Meregalli, & Berti, 1990;McGlynn & Schacter, 1989). Pure psychodynamic theories, involving for example denial or depression, are challenged to some degree as comprehensive explanations of disturbances in awareness by the more frequent link between anosognosia and right hemisphere dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Other neurological patients, especially those suffering hemiplegia, hemianesthesia, and hemianopia, have no awareness of their deficits--a condition called anosognosia (for a review, see McGlynn & Schacter, 1989). Given that anosognosic patients do not acknowledge their deficits, understanding how they make sense of their disabilities should shed new light on the process of causal attribution regarding the self (Kihlstrom & Tobias, 1991).…”
Section: A Neuropsychological Approach To Issues In Social and Personmentioning
confidence: 99%
“…Poor performance on intelligence tests has been associated with self-awareness in TBI, with lower post-injury verbal intelligence associated with greater impaired awareness (Anderson & Tranel, 1989). However, this relationship was not found in other studies (Ownsworth et al, 2002;Trudel et al, 1998), and individuals with intact intellectual functioning have also shown deficits in impaired awareness (McGlynn & Schacter, 1989). Executive dysfunction has been associated with ISA in many studies (Allen & Ruff, 1990;Noe et al, 2005;Ownsworth et al, 2002), but this association was not found, or only partially replicated in others (Bogod et al, 2003;Trudel et al, 1998).…”
Section: Introductionmentioning
confidence: 98%